The last words of Will Wolfkin - Knight, Steven 1959- (Walden Pond Press / HarperCollins, 2010)
Fourteen-year-old Toby, paralyzed since birth and raised in a convent, suddenly finds himself capable of movement and speech when his long-time companion, a cat, takes him on a magical and mysterious journey to Iceland